2019
DOI: 10.1021/acsabm.8b00774
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Sterically Stabilizes Spherical Nanoparticle-Supported Lipid Bilayers

Abstract: While it is generally accepted that neuronal protein α-synuclein binds to highly curved and highly charged lipid membranes, its biological function beyond binding remains unknown despite its fundamental link to Parkinson’s disease. Herein, we utilize spherical nanoparticle lipid bilayers (SSLBs) to recapitulate the charge and curvature limit of membrane organelles with which α-synuclein associates and probe how α-synuclein affects SSLB structure and dynamics as a proxy for interorganelle interactions. Small-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…and affinity (apparent dissociation constant of 92 and 42 μM, respectively) to SSLBs designed to reflect the membrane charge and size limit of synaptic vesicles (50% charged lipid and 70 nm diameter, respectively). [11] Reflecting in vitro and in vivo data of the relatively dilute binding density of S, [12,13] the protein-to-outer lipid ratio for all our experiments was 1:80 (a ratio that did not disrupt the supported lipid bilayer, Figure S1). [11] To probe the force response of this steric stabilization afforded by S at this protein-to-outer lipid ratio, SAXS was used to investigate the higher order structure of S-bound SSLBs as a function of increasing polyethylene glycol, MW = 10,000 (10kPEG), an inert osmotic depletant known to induced depletion attraction between solidsupported membrane surfaces.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…and affinity (apparent dissociation constant of 92 and 42 μM, respectively) to SSLBs designed to reflect the membrane charge and size limit of synaptic vesicles (50% charged lipid and 70 nm diameter, respectively). [11] Reflecting in vitro and in vivo data of the relatively dilute binding density of S, [12,13] the protein-to-outer lipid ratio for all our experiments was 1:80 (a ratio that did not disrupt the supported lipid bilayer, Figure S1). [11] To probe the force response of this steric stabilization afforded by S at this protein-to-outer lipid ratio, SAXS was used to investigate the higher order structure of S-bound SSLBs as a function of increasing polyethylene glycol, MW = 10,000 (10kPEG), an inert osmotic depletant known to induced depletion attraction between solidsupported membrane surfaces.…”
Section: Resultssupporting
confidence: 62%
“…[11] Reflecting in vitro and in vivo data of the relatively dilute binding density of S, [12,13] the protein-to-outer lipid ratio for all our experiments was 1:80 (a ratio that did not disrupt the supported lipid bilayer, Figure S1). [11] To probe the force response of this steric stabilization afforded by S at this protein-to-outer lipid ratio, SAXS was used to investigate the higher order structure of S-bound SSLBs as a function of increasing polyethylene glycol, MW = 10,000 (10kPEG), an inert osmotic depletant known to induced depletion attraction between solidsupported membrane surfaces. [14] The azimuthally averaged line shape of S-bound SSLBs revealed that at sufficient PEG concentration (C 10kPEG = 10.5 wt/vol %, corresponding to a critical osmotic pressure P C ~ 1.3 x 10 5 Pa), there was an onset of a correlation peak (q ~ 0.0092 Å -1 ) consistent with the nearest-neighbor distance between a pair of SSLBs (Figure 1).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Many of these applications are summarized in recent reviews (Leheny, 2012;Shpyrko, 2014;Sinha et al, 2014;Madsen et al, 2016;Sandy et al, 2018). Partially driven by XPCS-applicable area detectors with increasingly high frame rates (Trapani et al, 2018;Zhang et al, 2020Zhang et al, , 2018Zinn et al, 2018;Pennicard et al, 2018;Redford et al, 2018;Maj et al, 2020;Allahgholi et al, 2019;Poikela et al, 2014) but also by emerging near-diffraction-limited storage rings (DLSRs) (Eriksson et al, 2014), a growing area of interest is XPCS applied to rapidly fluctuating and often weakly scattering soft materials (Vodnala et al, 2018;Mö ller et al, 2019;Chung et al, 2019;Zhang et al, 2019;Dallari et al, 2020;Nigro et al, 2020;Frenzel et al, 2019;Yavitt et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to supported bilayers on a planar surface 8 , supported lipid bilayers can be formed on spherical silica nanoparticles, presenting a relatively well-behaved membrane surface separate from the silica support by a thin aqueous layer 9 . Such supported bilayers have been used as substrates in a number of nano-biological applications [10][11][12][13][14] . Here, we report the use of supported bilayers on silica nanoparticles (SLB-nanoparticles) as a substrate for influenza virus fusion.…”
mentioning
confidence: 99%